H Hubungan Pola Hidup Terhadap Kadar Gula Darah Penderita Diabetes Mellitus Tipe 2 - Syarifah Rini; Onieqie Ayu Dhea Manto; Angga Irawan (LPPM Universitas Sari Mulia, 2022)
Background: Diabetes Mellitus is a group of metabolic diseases with characteristics of hyperglycemia (high blood sugar levels) that occur due to abnormalities in insulin secretion, insulin action or both. Type 2 diabetes mellitus must always pay attention to lifestyle to stay healthy or by always paying attention to the 5 pillars of diabetes mellitus management, namely food, medicine, exercise, glycemic control, foot care and most importantly diet and diet to prevent an increase in blood sugar levels blood and avoid complications because many people still do not pay attention to diet and diet patterns. Objective: To find out the relationship between lifestyle and blood sugar levels of dm type 2 sufferers at UPT Puskesmas Terminal Banjarmasin Method: : This study uses quantitative methods and uses a cross sectional study approach. The number of samples as many as 73 people with putposive sampling technique. Result: Chi Square correlation test results with = 0,05. From the results of the Chi Square statistical test, a significant value of 0.441> 0.05 showed that there was no relationship between lifestyle and blood sugar levels in type 2 DM patients. Conclusion: Increased blood sugar levels are not only influenced by lifestyle but also influenced by other factors such as diet, smoking, foot care and diabetes self-care